Device-related complications in subcutaneous versus transvenous ICD: a secondary analysis of the PRAETORIAN trial. (6th October 2022) - Knops, Reinoud E; Pepplinkhuizen, Shari; Delnoy, Peter Paul H M; Boersma, Lucas V A; Kuschyk, Juergen; El-Chami, Mikhael F; Bonnemeier, Hendrik; Behr, Elijah R; Brouwer, Tom F; Kaab, Stefan; Mittal, Suneet; Quast, Anne-Floor B E; et al.
Structured Graphical Abstract: Structured Graphical Abstract Shown is the summary of the main endpoints of the manuscript: device-related complications in the subcutaneous and transvenous ICD: a secondary analysis of the PRAETORIAN trial. ICD, implantable cardioverter-defibrillator. Abstract: Background: The subcutaneous implantable cardioverter-defibrillator (S-ICD) is developed to overcome lead-related complications and systemic infections, inherent to transvenous ICD (TV-ICD) therapy. The PRAETORIAN trial demonstrated that the S-ICD is non-inferior to the TV-ICD with regard to the combined primary endpoint of inappropriate shocks and complications. This prespecified secondary analysis evaluates all complications in the PRAETORIAN trial. Methods and results: The PRAETORIAN trial is an international, multicentre, randomized trial in which 849 patients with an indication for ICD therapy were randomized to receive an S- ICD ( N = 426) or TV-ICD ( N = 423) and followed for a median of 49 months. Endpoints were device-related complications, lead-related complications, systemic infections, and the need for invasive interventions. Thirty-six device-related complications occurred in 31 patients in the S-ICD group of which bleedings were the most frequent. In the TV-ICD group, 49 complications occurred in 44 patients of which lead dysfunction was most frequent (HR: 0.69; P = 0.11). In both groups, half of all complications were within 30 days after implantation. Lead-related complications and systemic infections occurred significantly less in the S-ICD group compared with the TV-ICD group ( P < 0.001, P = 0.03, respectively). Significantly more complications required invasive interventions in the TV-ICD group compared with the S-ICD group (8.3% vs. 4.3%, HR: 0.59; P = 0.047). Conclusion: This secondary analysis shows that lead-related complications and systemic infections are more prevalent in the TV-ICD group compared with the S-ICD group. In addition, complications in the TV-ICD group were more severe as they required significantly more invasive interventions. This data contributes to shared decision-making in clinical practice.